Checking the standardization of the use and occupation of urban watershed armasreduto in 2013, Belém/PA - Dias, Rafael Pompeu; Silva, Marcela Ferreira da (Revista Hipótese, 2017)
The present study aims to characterize and analyze the land use in the Armas- Reduto basin in 2013, as the area is one of the most valued economically in Bethlehem, located on the first asset league from the city and with an area of 3,778. 535.99 m², came undergoing several transformations in its scope over the decades, then, it is important to analyze how their occupation and use takes place today, from using literature searches to the use of a Geographical Information System (GIS ), noting the huge presence of residential areas (33,20%), with a tendency to increase more and more, due to its location and for being a long time inserted in the urban context of Bethlehem, soon, through the various urban transformations to become what it is today , an area with its diversity that mixes the past in its historic core and the present, with its most recent occupations.
Keywords: Mapping; Environment; Geographic Information System